Technology of Increasing Physical Activity of University Students = Metody zwiększania aktywności fizycznej studentów szkół wyższych : ст. - Griban, G. P. et.al.; Semeniv, S. (Zhytomyr Ivan Franko State University ; Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies, 2022)
Modern society requires the theory and practice of higher education institutions (HEI) to direct the accumulated scientific experience at the basis of the formation of a new structure of competent professionals who can think creatively, navigate in the information space, master worldview paradigms on their own and systematically maintain their health and high mental and physical capacity.
Keywords: physical activity; fitness; фізична культура і спорт; фітнес